The Role of Children in Family Decision Making a Theoretical Review - Sri Rejeki Ekasasi (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
Family is the basic unit where most individuals learn about product categories, how to consume it, and soon. So, understanding family buying behavior is very important. It used to be that husband and wife hold dominant influence family decision-making process. However, now, their role is changing. Today, children’s role in family decision-making process is also significant today. Their influence relates to a wide variety of products needed by their family, or not just to the items that directly relate to their need, such as toys or foods. This means that, to market successfully to the children, marketers must understand children’s buying decision making process and what media that can be used to socialize their products to them. Key words: family decision-making, children’s role in family decision making, consumer socialization.